A comprehensive assessment of mercury exposure in penguin populations throughout the Southern Hemisphere: using trophic calculations to identify sources of population-level variation - Brasso, Rebecka L. (2015)
The wide geographic distribution of penguins (Order Sphenisciformes) throughout the Southern Hemisphere provided a unique opportunity to use a single taxonomic group as biomonitors of mercury among geographically distinct marine ecosystems. Mercury concentrations were compared among ten species of penguins representing 26 geographically distinct breeding populations. Mercury concentrations were relatively low (62.00 ppm) in feathers from 18/26 populations considered. Population-level differences in trophic level explained variation in mercury concentrations among Little, King, and Gentoo penguin populations. However, Southern Rockhopper and Magellanic penguins breeding on Staten Island, Tierra del Fuego, had the highest mercury concentrations relative to their conspecifics despite foraging at a lower trophic level. The concurrent use of stable isotope and mercury data allowed us to document penguin populations at the greatest risk of exposure to harmful concentrations of mercury as a result of foraging at a high trophic level or in geographic ‘hot spots’ of mercury availability.